2008
DOI: 10.1111/j.1742-7843.2008.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine Improves the Clinical Conditions of Mustard Gas‐Exposed Patients with Normal Pulmonary Function Test

Abstract: Administration of N-acetylcysteine may be effective in diseases caused by oxidative-antioxidative imbalance. We aimed to determine the effect administration for 4 months of N-acetylcysteine (1200 mg daily) on sulfur mustard-induced bronchiolitis obliterans in patients with normal pulmonary function test. In a double-blind clinical trial, 144 patients with bronchiolitis obliterans due to sulfur mustard and bronchiolitis obliterans syndrome class 0, randomly entered to group 1 (n = 72, N-acetylcysteine) and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Moreover, mediations that enhance the antioxidant supply, such as N-acetylcysteine and Curcumin, can be effective in both improving cardiovascular system health (47,48) and treating the late complications of SM (49,50). How-…”
Section: Biochemical and Laboratory Findingsmentioning
confidence: 99%
“…Moreover, mediations that enhance the antioxidant supply, such as N-acetylcysteine and Curcumin, can be effective in both improving cardiovascular system health (47,48) and treating the late complications of SM (49,50). How-…”
Section: Biochemical and Laboratory Findingsmentioning
confidence: 99%
“…The exact mechanism of late pulmonary complication of SM exposure are not fully defined (14).Although the pathogenesis of COPD has completely determined and is mainly dependent on chronic inflammation and oxidative stress following activation of airway inflammatory cells, but there are few studies about the inflammatory basis of mustard lung (8,9,15).The pathological studies have shown that mustard lung is a neutrophilic / lymphocytic disorder (16,17).Also bronchiolar disease with varying degrees of inflammation as the main pathological finding, was demonstrated in a recent pathologic study in patients with sulfur mustard injury (18 ). According to the previous pathological studies, it seems that activation of inflammatory cells and generation of reactive oxygen species resulting in oxidative stress be involved (16,17).…”
Section: Pathogenesismentioning
confidence: 99%
“…According to the previous pathological studies, it seems that activation of inflammatory cells and generation of reactive oxygen species resulting in oxidative stress be involved (16,17). It has been shown that decreased glutathione and increased serum malondialdehyde levels in mustard lung patients can be an indicator of oxidative-antioxidative system imbalance (16).…”
Section: Pathogenesismentioning
confidence: 99%
“…Neutrophils can accelerate the overproduction of ROS by NADPH oxidase, myeloperoxidase and xanthine oxidase activation [7,9]. In addition, they secret proteases, which in turn manufacture ROS [4]. Formation of ROS leads to oxidative stress and macromolecular damage, which triggers intricate signaling pathways and modulate gene expression, causing a series of SM-associated toxic responses [10].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term complications of SM exposure are much serious than acute effects [1][2][3]. About 100,000 Iranians were exposed to chemical warfare agents, and 40,000 people suffer from pulmonary diseases such as asthma, chronic bronchiectasis and pulmonary fibrosis [3,4]. Bronchiolitis obliterans (BO) is the main long-term respiratory pathology in chemical victims of SM, which is a complex inflammatory disease with both airway and parenchymal lung injury [1,5].…”
Section: Introductionmentioning
confidence: 99%